Implementasi Teknologi Augmented Reality (AR) dalam Pembelajaran Kaffah sebagai Upaya Peningkatan Kebermaknaan dan Penguasaan Konsep Mahasiswa Calon Guru - Syahrial A.; Joni Rokhmat; Kosim Kosim; Muh. Makhrus; Himawati Himawati (Kappa Journal, 2025)
This study aims to develop Augmented Reality (AR)–based learning media integrated into Kaffah Learning and to determine its feasibility, practicality, and effectiveness in enhancing meaningful learning and conceptual understanding among prospective teacher students. The research employed a Research and Development (R&D) approach using the ADDIE model, consisting of the stages of analysis, design, development, implementation, and evaluation. Expert validation was conducted to assess the media's feasibility, while practicality was measured through implementation observations and student response questionnaires. Effectiveness was evaluated using pretest–posttest results analyzed with N-Gain. The validation results show that the developed media meets the feasibility criteria with an average score of 89.75% (very feasible category). The practicality test obtained an average score of 88.33%, indicating that the media is highly practical and easy to use during the learning process. The effectiveness test produced an N-Gain value of 0.76 (high category), demonstrating a significant improvement in students’ conceptual understanding. The AR-based media also contributed to strengthening meaningful learning, particularly in indicators of personal relevance, clarity, and conceptual meaning. In conclusion, the AR-based Kaffah Learning media is declared feasible, practical, and effective for supporting physics learning for prospective teachers. The media successfully integrates scientific concepts, interactive visualization, and Islamic values, offering a meaningful and holistic learning experience aligned with 21st-century educational demands.